2021
DOI: 10.1111/jth.15451
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor upregulation is associated with SARS‐CoV‐2 in the lungs of COVID‐19 patients

Abstract: Background: A substantial proportion of patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) develop severe/critical coronavirus disease 2019 (COVID-19) characterized by acute respiratory distress syndrome (ARDS) with thrombosis. Objectives:We tested the hypothesis that SARS-CoV-2--induced upregulation of tissue factor (TF) expression may be responsible for thrombus formation in COVID-19. Methods:We compared autopsy lung tissues from 11 patients with COVID-19-associated ARDS with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…Elevated levels of TF and increased TF patient with COVID-19 compared to non-COVID-19 patients. 18 , 50 The current study found significantly increased levels of TF-bearing MVs in the circulation of patient group, which is similar to previously published findings related to COVID-19 18 , 21 and viral infections. 17 In COVID-19, TF-bearing MVs have been suggested to play a role in thrombosis and even the severity and mortality.…”
Section: Discussionsupporting
confidence: 92%
“…Elevated levels of TF and increased TF patient with COVID-19 compared to non-COVID-19 patients. 18 , 50 The current study found significantly increased levels of TF-bearing MVs in the circulation of patient group, which is similar to previously published findings related to COVID-19 18 , 21 and viral infections. 17 In COVID-19, TF-bearing MVs have been suggested to play a role in thrombosis and even the severity and mortality.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, patients with COVID-19 have been shown to have elevated levels of tissue factor laden microvesicles circulating in their blood, along with other markers of the extrinsic coagulation cascade ( Rosell et al, 2021 ). Further, autopsy studies of COVID-19 patients have also found that tissue factor protein expression is approximately doubled in the lungs of patients that succumbed to COVID-19 ( Subrahmanian et al, 2021 ). Tissue factor upregulation in the BALF of COVID-19 patients has also been observed at the RNA level using both single cell and bulk RNA-sequencing, and the observed increase correlated with severity ( FitzGerald et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This method of data reporting obscures the extremely low counts for many genes of interest. Many other publications in the field, including bioinformatics analyses, in-vitro studies, clinical research, and post-clinical autopsies directly contradict the findings of Mast et al ( Subrahmanian et al, 2021 ; Rosell et al, 2021 ; FitzGerald et al, 2021 ). The initial publication of inaccurate findings could have been avoided by applying quality control standards to the libraries included in the analysis.…”
Section: Introductionmentioning
confidence: 88%
“…COVID-19 patients show elevated TF activity in circulating extracellular vesicles associated with disease severity and mortality [120]. Pulmonary histopathology studies with the characterization of CD61+ platelet thrombi in COVID-19 patients with ARDS showed that CD61+ areas were higher in COVID-19 vs. non-COVID-19 ARDS samples [121]. Interestingly, the same authors found that higher levels of fibrin and activated platelets in PF4-positive thrombi correlated to high TF protein expression throughout lung tissue samples in which both arterial and venous thrombi and microangiopathy were observed [121].…”
Section: Sars-cov-2 Effects On Plateletsmentioning
confidence: 99%